A Multilayered Approach to Public Diplomacy Evaluation: Pathways of Connection. Issue 5 (26th October 2017) - Sevin, Efe
Abstract : This article presents a multilayered framework, called pathways of connection, as an approach to public diplomacy evaluation. It is well established both in the study and practice of public diplomacy that evaluation is a daunting task, mostly due to the complex and convoluted nature of the concept. To overcome such obstacles, the proposed framework first defines public diplomacy as a foreign policy tool. This definition is then used to state that the only success criterion for a public diplomacy project is its contribution to advancing national interests, regardless of the type of the project or the practitioner country. Second, three layers on which the outcomes of public diplomacy projects can be observed are described by incorporating mainstream international relations theories in the practice of public diplomacy. Third, pathways of connection are introduced to explain how the changes in target audiences contribute to the advancement of national interests.